Thermal Stability of Functionally Graded Graphene Platelet Reinforced Composites - Kiani , Yaser (Journal of Composites and Compounds, 2025)
The thermal stability of functionally graded graphene platelet-reinforced composites (FG-GPLRCs) is influenced by the distribution and weight fraction of graphene platelets (GPLs). Different grading patterns, such as FG-X and FG-O, affect the critical buckling temperature, with FG-X providing the highest thermal resistance. The Halpin-Tsai model is commonly used to estimate elasticity modulus, while other properties are evaluated using the rule of mixtures. Studies indicate that a laminated structure with a limited number of layers can effectively mimic a continuously graded composite, making FG-GPLRCs a promising choice for high-temperature applications.